Becoming a translator an introduction to the theory and practice of translation - Robinson, Douglas 1954- (Routledge, 2020)
Fusing theory with advice and information about the practicalities of translating, Becoming a Translator is the essential resource for novice and practicing translators. The book explains how the market works, helps translators learn how to translate faster and more accurately, as well as providing invaluable advice and tips about how to deal with potential problems, such as stress. The fourth edition has been revised and updated throughout, offering: a whole new chapter on multimedia translation, with a discussion of the move from "intersemiotic translation" to "audiovisual translation," "media access" and "accessibility studies" new sections on cognitive translation studies, translation technology, online translator communities, crowd-sourced translation, and online ethnography "tweetstorms" capturing the best advice from top industry professionals on Twitter student voices, especially from Greater China Including suggestions for discussion, activities, and hints for the teaching of translation, and drawing on detailed advice from top translation professionals, the fourth edition of Becoming a Translator remains invaluable for students and teachers of Translation Studies, as well as those working in the field of translation